1996
DOI: 10.1111/j.1348-0421.1996.tb01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Expression of CD20 Antigen (Pan B Cell Marker) in Activated Lymph Node T Cells

Abstract: In contrast to the case of peripheral T cells, the surface expression of CD20 antigen and the expression of CD20 mRNA in monkey lymph node (LN) T cells underwent a noticeable increase when they were cultured with mitogen and interleukin-2 (IL-2). To confirm in vivo regulation of CD20 expression during the activation of LN T cells, we examined LNs derived from monkeys experimentally inoculated with simian immunodeficiency virus (SIV). Significant expression of CD20 antigen was detected in the T cells of the LNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Although this could be the result of nonspecific T-cell binding, no increased background staining was observed with the isotype mAb. Notably, CD20 has been identified as an activation marker on T cells in simian immunodeficiency virus (SIV)-infected rhesus monkeys (28). Positive staining was also found after PHA activation of PBMC from the owl monkey (Aotus lemurinus griseimembra; González et al, unpublished data).…”
Section: Resultsmentioning
confidence: 94%
“…Although this could be the result of nonspecific T-cell binding, no increased background staining was observed with the isotype mAb. Notably, CD20 has been identified as an activation marker on T cells in simian immunodeficiency virus (SIV)-infected rhesus monkeys (28). Positive staining was also found after PHA activation of PBMC from the owl monkey (Aotus lemurinus griseimembra; González et al, unpublished data).…”
Section: Resultsmentioning
confidence: 94%
“…However, it has not been clarified whether normal immature T cells (normal counterpart of T cell ALL blasts) expressing CD20 exist in humans. It was reported that some mature T cells from monkey lymph nodes, not from peripheral blood, gained in cell surface of CD20 after activating with interleukin-2 and concanavalin A [7]. Such activation usually induces blastoid transformation of T cells.…”
Section: Discussionmentioning
confidence: 98%
“…IFN-a (500-1000 U/ ml, 24-48 h) induces significant upregulation of CD20 on peripheral blood lymphocytes of patients with B-CLL with no significant increase of CD20 on normal lymphocytes . Activation of lymph node T cells by mitogen and IL-2 induces CD20 expression (Murayama et al, 1996). IFN-g (100-1000 U/ ml, 48-72 h) augments CD20 surface expression on human myeloma cells (Treon et al, 2001;Jazirehi et al, 2002).…”
Section: Modulation Of Cd20 Expressionmentioning
confidence: 99%